A New Approach for Infrared Temperature Measurement Sensor Systems and Temperature Control for Domestic Induction Hobs - Altuntas, Hakan; Arslan, Mehmet Selcuk (MDPI, 2025)
The accurate measurement of cooking vessel temperatures in induction hobs is crucial for ensuring optimal cooking performance and safety. To achieve this, improvements in existing measurement methods such as thermocouples, thermistors, and infrared (IR) temperature sensors are being explored. However, traditional IR sensors are sensitive to interference from the heated glass ceramic, severely affecting accuracy. This challenge is addressed by introducing a new sensor system with an optical filter designed to match the glass ceramic's optical characteristics. The theoretical model presented here proposes the separation of the total radiation reaching the IR sensor into components emitted by the cooking vessel and the glass ceramic. However, the radiation component originating from the glass ceramic mentioned here is significantly higher than the radiation component of the cooking vessel, which creates difficulties in measuring the temperature of the cooking vessel. Simulations and real cooking experiments validate the model and demonstrate that the optic filter significantly increases the contribution of pot radiation to the sensor measurement. This causes a more accurate reflection of the actual cooking vessel temperature, leading to improved temperature control and enhanced cooking experiences in domestic induction hob appliances. This research contributes to the field by innovatively addressing challenges in real-time temperature control for induction cooking appliances. The elimination of pot dependence and improved accuracy have significant implications for cooking efficiency, safety and food quality.
Keywords: home appliances; induction heating; induction hobs; infrared temperature sensor; non-contact temperature measurement; radiation theory; sensor systems; temperature control; thermopile; APPLIANCES; Chemistry; Engineering; Instruments & Instrumentation